MiR‐125a/b inhibits tumor‐associated macrophages mediated in cancer stem cells of hepatocellular carcinoma by targeting CD90. Issue 3 (9th December 2018) - Wang, Yufeng; Wang, Bingyi; Xiao, Shuai; Li, Yang; Chen, Quanning
Abstract: Cancer stem cells promote tumorigenesis and progression of hepatocellular carcinoma (HCC). Recently, emerging evidence indicates tumor‐associated macrophages (TAMs) play an important role in tumor progression. However, TAMs often occurs with unknown mechanisms. As an important mediator in intercellular communications, exosomes secreted by host cells mediate the exchange of genetic materials and proteins, which involves tumor aggressiveness. The aim of the study was to investigate whether exosomes derived from TAMs mediate stem cell properties in HCC. TAMs were isolated from the tissues of HCC. microRNA (miRNA) expression profiles of TAMs were analyzed using miRNA microarray. In vitro cell coculture was further conducted to investigate the crosstalk between TAMs and tumor cells mediated by TAMs exosomes. In this study, we showed that TAMs exosomes promote HCC cell proliferation and stem cell properties. Using miRNA profiles assay, we identified significantly lower levels of miR‐125a and miR‐125b in exosomes and cell lysate isolated from TAMs. Functional studies revealed that the HCC cells were treated with TAM exosomes or transfected with miR‐125a/b suppressed cell proliferation and stem cell properties by targeting CD90, a stem cell marker of HCC stem cells. The study indicated that miR‐125a/b targeting CD90 played important roles in cancer stem cells of HCC. Abstract : The study demonstrated that the in vitro coculture of tumor‐associated macrophages ‐derived exosomes with low levels of miR‐125a and miR‐125b promoted hepatocellular carcinoma (HCC) cell proliferation, sphere cell formation and metastasis by downregulating CD90, a stem cell marker of HCC.